2016
DOI: 10.1088/2053-1591/3/12/125003
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and high fluence induced ripple rotation on Si(100) surface

Abstract: Topography evolution of Si(100) surface due to oblique incidence low energy ion beam sputtering (IBS) is investigated. Experiments were carried out at different elevated temperatures from 20 • C to 450 • C and at each temperature, the ion fluence is systematically varied in a wide range from ∼ 1×10 18 cm −2 to 1×10 20 cm −2 . The ion sputtered surface morphologies are characterized by atomic force microscopy and high-resolution cross-sectional transmission electron microscopy. At room temperature, the ion sput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…It is advantageous for its ability of nanostructuring in large area (order of cm 2 ) within few minutes in just one step without any mask, resist or chemical hazards. Twodimensional dot and one-dimensional ripple topographies are generally found to develop on the surfaces of semiconductors due to IBS at room temperature [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is advantageous for its ability of nanostructuring in large area (order of cm 2 ) within few minutes in just one step without any mask, resist or chemical hazards. Twodimensional dot and one-dimensional ripple topographies are generally found to develop on the surfaces of semiconductors due to IBS at room temperature [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the pattern formation has been studied mostly with Si [3][4][5][6][7][8] because of its easy availability and technological importance in semiconductor industry [9].…”
Section: Introductionmentioning
confidence: 99%
“…Further drawbacks are related with master or mask deterioration and to the limited versatility in the design of the mask. Conversely, large area and low cost nanofabrication can be achieved via bottom-up approaches based on self-assembly or self-organization, e.g., recurring to defocused ion beam sputtering (IBS) [43][44][45] at the expense of a reduced uniformity of the patterns on large scale.…”
Section: Resultsmentioning
confidence: 99%
“…On Si(100) surfaces, it was obtained that the wavelength increased with temperature due to a surface diffusion mechanism [99] whereas on Si(111) surfaces a more complex behaviour was observed as the pattern morphology evolved with temperature and changed its orientation [100]. The other report to be considered deals with a temperature range from room temperature up to 350 • C [190], which is similar to those employed for IBI with concurrent co-deposition. In this work, it was found that the surface roughness was constant up to 350 • C to decrease for higher temperatures.…”
Section: Target Temperaturementioning
confidence: 97%